Burden of Disease for Urethral Stricture Managed by Repeat Endoscopic Treatment vs Single Endoscopic Treatment or Urethroplasty in the Veterans Affairs Population. Issue 4 (July 2018) - Rude, Temitope L.; Khurana, Kiranpreet; Yamaguchi, Yuka; Walter, Dawn; Makarov, Danil; Zhao, Lee C.
Abstract : Introduction : Male urethral stricture disease is a challenging urological condition that affects nearly a third of men 65 years old or older. Management options include dilation and urethrotomy as well as urethroplasty, an open approach with increased morbidity and durability. Presently optimal management remains debated. In this study we focus on emergent procedures required by male patients in the Veterans Health Administration after stricture treatment as an indicator of clinically significant complications, comparing treatment approaches. Methods : We performed an institutional review board approved, retrospective, cohort study of male veterans with urethral stricture from 2005 to 2014. Our independent variable was immediate or delayed urethroplasty or continued endoscopic treatments. Our dependent variable was a stricture related procedure performed in the emergent or urgent care setting. We used a binary logistic regression model to model the likelihood of an adverse outcome as predicted by treatment type. Results : In our cohort of 9, 632 patients 1.8% underwent immediate urethroplasty and 3% underwent delayed urethroplasty. Of the operated men 5.3% had an adverse outcome (5% following delayed urethroplasty or continued endoscopic treatments and 1% after immediate urethroplasty, p = 0.04). On multivariate analysis repeat endoscopy and delayed urethroplasty trended toward worsening odds of adverse outcomes (p = 0.07 and p = 0.08, respectively). Conclusions : In the Veterans Health Administration system men who undergo repeated scheduled endoscopic treatments for urethral stricture may be at increased risk for emergent procedures, even if they eventually progress to urethroplasty, compared to men who undergo urethroplasty immediately after a failed endoscopic intervention.